Morphological trait variation of the immature liberica coffee (Coffea liberica) from West Java applied difference of coffee husk compost and biofertilizer - YUDITHIA MAXISELLY; FERRANI RIEFALINA NAFY; INTAN RATNA DEWI ANJARSARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maxiselly Y, Nafy FR, Anjarsari IRD. 2023. Morphological trait variation of the immature liberica coffee (Coffea liberica) from West Java applied difference of coffee husk compost and biofertilizer. Biodiversitas 24: 5988-5994. Improving the growth of immature Liberica coffee is achievable through fertilizer application. This is because nutrients can be provided to plants by microorganisms from organic and biological fertilizers. Therefore, this research aimed to determine the response and the best treatment for applying coffee husk compost and consortium biofertilizer, which contained nitrogen-fixing and phosphate-solubilizing bacteria on the growth of immature Liberica plant. The experiment was held at Ciparanje Research Center, Padjadjaran University, West Java, with an altitude of ±750 meters above sea level (masl) from January to May 2023. Furthermore, a randomized complete block design (RCBD) was conducted with six treatment combinations. Each treatment was repeated four times including control (Urea 20 g.plant-1 + SP36 25 g.plant-1 + KCl 15 g.plant-1), solid coffee husk compost 3 kg.plant-1, liquid coffee husk compost 80 mL.L-1, biofertilizer 10 mL.L-1, solid coffee husk compost 3 kg.plant-1 + biofertilizer 10 mL.L-1, and liquid coffee husk compost 80 mL.L-1 + biofertilizer 10 mL.L-1. The results showed that biofertilizer significantly affected for increasing the morphology trait of immature Liberica coffee, namely the plant height, stem diameter, number of primary branches, length of primary branches, leaf area, and leaf chlorophyll index. The best treatment for immature Liberica plants was the liquid coffee husk compost 80 mL.L-1 + biofertilizer 10 mL.L-1. Based on this research, the combination of coffee husk compost, especially the liquid form, and biofertilizer is the potential application to boost the immature Liberica coffee growth.